KEMAMPUAN CAPITAL, ASSET, EARNINGS, DAN LIQUIDITY MEMENGARUHI PERTUMBUHAN LABA PADA LPD KABUPATEN BADUNG - Paramithari, Ni Made Pradnya; Sujana, I Ketut (E-Jurnal Akuntansi; Vol 17 No 1 (2016), 2016)
LPD earning growth reflects the improved financial performance LPD and high public confidence and satisfaction of the people. This study aims to test empirically the effect of CAR, KAP, PPAP, ROA, ROA, and LDR LACLR to profit growth. The population in this study were all LPD in the Badung regency period 2011-2013 with a simple random sampling method. Based on the method of determining the sample obtained a sample of 54 LPD, after processing, the data affected by outliers 5 LPD, so that the number of samples to 49 LPD. Data were analyzed using multiple linear regression analysis. The results showed that the CAR, PPAP, ROA, and LACLR positive effect on earning growth. KAP and LDR negative effect on earning growth. BOPO no effect on earning growth.
Keywords: Earning growth, CAR, KAP, PPAP, ROA, ROA, LACLR, LDR